Business process change a business process management guide for managers and process professionals - Harmon, Paul 1942- (Morgan Kaufmann, 2014)
This edition provides a balanced view of the field of business process change. Paul Harmon offers concepts, methods, cases for all aspects and phases of successful business process improvement. Updated and added for this edition is new material on the development of business models and business process architecture development, on integrating decision management models and business rules, on service processes and on dynamic case management, and on integrating various approaches in a broad business process management approach. New to this edition: how to develop business models and business process architecture; how to integrate decision management models and business rules; new material on service processes and on dynamic case management; learn to integrate various approaches in a broad business process management approach; extensive revision and update addresses Business Process Management Systems, and the integration of process redesign and Six Sigma. --